Amino sugars as indicator of organic matters source and diagenesis in the surface sediments of the East China Sea. (February 2019) - Ren, Chengzhe; Yuan, Huamao; Song, Jinming; Duan, Liqin; Li, Xuegang; Li, Ning; Zhou, Bu
Highlights: Bacteria were a major source of AS and OM in the sediments of the ECS. In nearshore, the OM was more labile than that in offshore area. As the algae bloom decline, the OM source transformed from plankton to bacteria. The settling plankton detritus provided food for benthic bacteria in summer. The estimation based on Mur showed the important contribution of bacterial OM. Abstract: Amino sugars (AS) were investigated to study the source, reactivity and bacterial contribution of organic matters (OM) in surface sediments of the East China Sea (ECS) both in summer and autumn in 2016, within and after the algae bloom, respectively. The content of AS was 0.48–7.23 μmol/(g dw) with a higher concentration in nearshore than that in offshore area and lower concentration in summer than that in autumn, which on average made up 3.65 ± 1.66% of TOC and 4.49 ± 1.98% of TN in the ECS surface sediments. The low average ratio of glucosamine/galactosamine (GlcN/GalN) (1.16 ± 0.15) indicated a major bacterial source of AS pool of the investigated area. Higher GlcN/GalN (1.30 ± 0.15 in summer and 1.21 ± 0.09 in autumn) and muramic acid (Mur) (8.8 ± 3.8 nmol/(mg C) in summer and 20.5 ± 10.3 nmol/(mg C) in autumn) and together with lower GlcN/Mur (29 ± 8 in summer and 16 ± 4 in autumn) content in nearshore than those in offshore area (GlcN/GalN: 1.11 ± 0.14 in summer and 1.09 ± 0.13 in autumn; Mur: 5.2 ± 1.7 nmol/(mg C) in summer and 10.4 ± 5 nmol/(mg C) in autumn; GlcN/Mur: 36 ± 9 in summer and 34 ± 11 in autumn) indicated more plankton detritus and a more labile nature of OM, and also relatively higher fresh bacteria contribution to OM in nearshore area, which was consistent with the higher concentrations of Chl- a in corresponding surface water. The transformation of plankton to bacteria source of OM from summer to autumn was revealed by the increased total hydrolysable amino sugars (THAS) and Mur concentration, C- and N-normalized yield of THAS, and also the decreased ratios of GlcN/GalN and GlcN/Mur in sediments in autumn. The correlation between Mur in sediments and Chl- a in surface water suggested that the real-time settling plankton detritus was one of the major food sources for benthic bacteria in summer but contributed little in autumn. Based on Mur, the relatively fresh bacteria OM contribution to TOC were 13.1% in summer and 28.5% in autumn. In summary, the composition of AS in the ECS surface sediments showed a major bacteria origin of OM and the bioavailability decreased from nearshore to offshore and also from summer to autumn. As the algae bloom decline, the flux of plankton detritus decreased and the OM source transformed from plankton to bacteria.